Real-life efficacy of vedolizumab on endoscopic healing in inflammatory bowel disease – A nationwide Hungarian cohort study. (1st February 2020) - Bor, Renáta; Fábián, Anna; Matuz, Mária; Szepes, Zoltán; Farkas, Klaudia; Miheller, Pál; Szamosi, Tamás; Vincze, Áron; Rutka, Mariann; Szántó, Kata; Bálint, Anita; Nagy, Ferenc; et al.
ABSTRACT: Background : GEMINI trials demonstrated the therapeutic efficacy of vedolizumab (VDZ) in Crohn's disease (CD) and ulcerative colitis (UC). Research design and methods : Aim of this study was to determine the real-life effectiveness of VDZ on endoscopic healing in the Hungarian nationwide cohort of inflammatory bowel disease (IBD) patients based on the changes on clinical and endoscopic scores. Every adult IBD patient in the country (121 UC and 83 CD) who completed the short-term VDZ therapy was enrolled, of which 72 UC and 52 CD patients could complete the long-term therapy. Results : The rates of endoscopic healing were substantially higher in UC compared with CD patients during the short- and long-term therapy (52.9% vs. 21.7%, p < 0.0001, and 51.4% vs. 21.2%, p = 0.015, respectively). In CD, the rate of endoscopic healing was lower at week 14 compared with week 22 (14.5% vs. 37.0%, p = 0.026). Prior anti-TNF-α therapy (88.73%) was not associated with a significant decrease in therapeutic response. The average disease duration was significantly lower in CD patients achieving endoscopic healing at week 52 (11.75 vs. 5.27 years, p = 0.007). Conclusions : VDZ therapy is an effective therapeutic option in anti-TNF-α refractory IBD. However, the endoscopic healing rate was substantially lower and showed a significant delay in CD compared with UC.